XIX ÁSIR ShAYÍRLARÍ ShÍǴARMALARÍNDA QOLLANÍLǴAN AYÍRÍM ETNOTOPONIMLER HAQQÍNDA - Abishov, G.M.; Amaniyazova, S.B. (ILIM hám JÁMIYET, 2025)
This article examines the ethnotoponyms used in the works of Karakalpak classical poets. Ethnotoponyms denote the names of geographical objects formed on the basis of the names of clans, tribes, peoples, and nations, and the reasons for their naming have been clarified. The currently used or unused types of these ethnotoponyms have been analyzed through the works of 19th-century poets.